When Signals are Lost in Aggregation: A Comparison of Language Marks and Competencies of Entering University Students - Fleisch, Brahm; Schöer, Volker; Cliff, Alan (South African Journal of Higher Education, 2016)
Although English Home Language and English First Additional Language marks from the National Senior Certificate (NSC) are used for university admission in South Africa, no studies have explored their predictive value. This paper shed light on English language marks and English language competence through a comparative analysis of NSC marks and National Benchmark Test in Academic Literacy test results for a cohort of first year education students at the University of the Witwatersrand. To provide in-depth insight, the analysis includes fine-grained analysis of specific academic language competencies. The results of the analysis in this study show that the same mark in Home Language and First Additional Language does not necessarily reflect the same level of English-language academic competence as measured by the NBT Academic Literacy test. On average, students that wrote the First Additional Language papers scored between .5 and .9 of a standard deviation below students who wrote the Home Language papers.